Effects of corporate social responsibility on brand reputation and brand identification with children - Pais, Madalena Sofia Sarmento de Figueiroa-Rêgo (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics